2015
DOI: 10.4254/wjh.v7.i11.1572
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 cytokines and their genotypes as predictors of hepatitis B virus related hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC), the predominant type of primary liver cancer, is one of the most serious life-threatening malignancies, worldwide. In majority of the cases, HCC develops after prolonged and persistent chronic liver disease. hepatitis B virus (HBV) or HCV infection is prominent etiological factors, attributing to this condition. It has been well documented that HBV, being the inducer of chronic inflammation, is the main causative agent in causing HCC, particularly in Asian countries. The HBV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 76 publications
4
41
0
1
Order By: Relevance
“…Moreover, IL-10 SNPs are associated with higher risk of HBV-related HCC in some populations (Shin et al, 2003c;Tseng et al, 2006;Wang et al, 2006). Further, as reported by Saxena et al (2014a) and Saxena and Kaur (2015), the CC/TA genotype of − 592 A/C and − 819 T/C to be in a significant positive association with HBV-related HCC and disease development. While Nieters et al (2005) showed that the wild and heterozygous genotypes had no significant association with HCC.…”
Section: Il-10supporting
confidence: 62%
“…Moreover, IL-10 SNPs are associated with higher risk of HBV-related HCC in some populations (Shin et al, 2003c;Tseng et al, 2006;Wang et al, 2006). Further, as reported by Saxena et al (2014a) and Saxena and Kaur (2015), the CC/TA genotype of − 592 A/C and − 819 T/C to be in a significant positive association with HBV-related HCC and disease development. While Nieters et al (2005) showed that the wild and heterozygous genotypes had no significant association with HCC.…”
Section: Il-10supporting
confidence: 62%
“…IFN‐γ is likely to be important in early host defense against infection, whereas T lymphocytes become the major source of IFN‐γ in the adaptive immune response . IL‐2, a pro‐inflammatory and strong immunoregulatory Th1 cytokines, affects various immune cells . IL‐4 plays a pivotal role in Th2 cell proliferation, cytokines production and IgE synthesis, while IL‐13 is important in the pathological features of disease …”
Section: Discussionmentioning
confidence: 99%
“…11 IL-2, a pro-inflammatory and strong immunoregulatory Th1 cytokines, affects various immune cells. 12 IL-4 plays a pivotal role in Th2 cell proliferation, cytokines production and IgE synthesis, while IL-13 is important in the pathological features of disease. 13 In this study, the concentration of IFN-c of COPD patients in both the acute exacerbation and remission was significantly higher than that in control group, and AECOPD group was slightly lower than in remission group.…”
Section: Discussionmentioning
confidence: 99%
“…Th cells play a critical role in the immune system responses regulation. These cells based on the cytokines production subdivide to Th1 or Th2 [20,21]. Th1 based response increases IFN-γ production which in turn has direct effect on the proliferation of Th1.…”
Section: Discussionmentioning
confidence: 99%